Tissue Engineering to Repair Diaphragmatic Defect in a Rat Model - G. P. Liao; Y. Choi; K. Vojnits; H. Xue; K. Aroom; F. Meng; H. Y. Pan; R. A. Hetz; C. J. Corkins; T. G. Hughes; F. Triolo; A. Johnson; et al. (Hindawi Limited, 2017)
Tissue engineering is an emerging strategy for repairing damaged tissues or organs. The current study explored using decellularized rat diaphragm scaffolds combined with human amniotic fluid-derived multipotent stromal cells (hAFMSC) to provide a scaffold, stem cell construct that would allow structural barrier function during tissue ingrowth/regeneration. We created an innovative cell infusion system that allowed hAFMSC to embed into scaffolds and then implanted the composite tissues into rats with surgically created left-sided diaphragmatic defects. Control rats received decellularized diaphragm scaffolds alone. We found that the composite tissues that combined hAFMSCs demonstrated improved physiological function as well as the muscular-tendon structure, compared with the native contralateral hemidiaphragm of the same rat. Our results indicate that the decellularized diaphragm scaffolds are a potential support material for diaphragmatic hernia repair and the composite grafts with hAFMSC are able to accelerate the functional recovery of diaphragmatic hernia.